636 SHORT-TERM OUTCOME FOR HIGH-RISK PATIENTS AFTER ESOPHAGECTOMY. (17th September 2021) - Plat, Victor; Stam, Wessel; Bootsma, Boukje; Straatman, Jennifer; Klausch, Thomas; Heineman, David; Peet, Donald; Daams, Freek
Abstract: : Transthoracic esophagectomy (TTE) for esophageal cancer facilitates mediastinal dissection, however it has a significant impact on cardiopulmonary status. High-risk patients may therefore be better candidates for transhiatal esophagectomy (THE) in order to prevent serious complications. This study addressed short-term outcome following TTE and THE in patients that are considered to have a higher risk of surgery-related morbidity. Methods: This population-based study included patients who underwent a curative esophagectomy between 2011 and 2018, registered in the Dutch Upper GI Cancer Audit. The Charlson comorbidity index was used to assign patients to a low-risk (score ≤ 1) and high-risk group (score ≥ 2). Propensity score matching was applied to produce comparable groups between high-risk patients receiving TTE and THE. Primary endpoint was mortality (in-hospital/30-day mortality), secondary endpoints included morbidity and oncological outcomes. Additionally, a matched subgroup analysis was performed, including only cervical reconstructions. Results: Of 5438 patients, 945 and 431 high-risk patients underwent TTE and THE respectively. After propensity score matching, mortality (6.3% vs 3.3%, P = 0.050), overall morbidity, Clavien-Dindo ≥3 complications, pulmonary complications, cardiac complications and re-interventions were significantly more observed after TTE compared to THE. A significantly higher mortality after TTE with a cervical reconstruction was found compared to THE (7.0% vs 2.2%, P = 0.020). Conclusion: Patients with a high Charlson comorbidity index predispose for a complicated postoperative course after esophagectomy, this was more outspoken after TTE compared to THE. In daily practice these outcomes should be balanced with the lower lymph node yield, but comparable positive node count and radicality after THE.